Clinical Outcomes of Offset Stem Couplers with or without Cone Augmentation in Revision Total Knee Arthroplasty - Fiedler, Benjamin; Bieganowski, Thomas; Singh, Vivek; Marwin, Scott; Rozell, Joshua C.; Schwarzkopf, Ran (The Journal of Knee Surgery, 2023)
Intramedullary stems are often required in patients undergoing revision total knee arthroplasty (rTKA) to achieve stable fixation. Significant bone loss may require the addition of a metal cone to maximize fixation and osteointegration. The purpose of this study was to investigate clinical outcomes in rTKA using different fixation techniques. We conducted a single-institution retrospective review of all patients who received a tibial and femoral stem during rTKA between August 2011 and July 2021. Patients were separated into three cohorts based on fixation construct: press-fit stem with an offset coupler (OS), fully cemented straight (CS) stem, and press-fit straight (PFS) stem. A subanalysis of patients who received tibial cone augmentation was also conducted. A total of 358 patients who underwent rTKA were included in this study, of which 102 (28.5%) had a minimum 2-year follow-up and 25 (7.0%) had a minimum 5-year follow-up. In the primary analysis, 194 patients were included in the OS cohort, 72 in the CS cohort, and 92 in the PFS cohort. When stem type alone was considered, there was no significant difference in rerevision rate (p = 0.431) between cohorts. Subanalysis of patients who received augmentation with a tibial cone demonstrated that OS implants led to significantly higher rates of rerevision compared with the other two stem types (OS: 18.2% vs. CS: 2.1% vs. PFS: 11.1%; p = 0.037). The findings of the present analysis demonstrate that CS and cones in rTKA may provide more reliable long-term outcomes compared with press-fit stems with OS.Level III Evidence Retrospective Cohort Study.
Keywords: offset stem; cemented straight stem; press-fit stem; cone; revision total knee arthroplasty; outcomes